Exports and economic growth: A causality analysis for Mexico - Cuadros Ramos, Ana María (Estudios Económicos de El Colegio de México, 2000)
We analyze the Granger causal relationship between openness and economic growth in Mexico. The results obtained indicate the absence of a causal relationship among different categories of exports and growth for the period 1983-1997. Nevertheless, it has been identified a significant positive causal relationship between the growth of imports, both in total and intermediate goods and the growth of output. Thus, the outcomes of this study suggest that even though the trade liberalization process has influenced positively economic growth, it has not only been through the theoretical gains associated to the export sector expansion. The positive effects have gone beyond that. They have been generated by both, favorable economic conditions related to the openness process and growth of exports which has provided the necessary foreign exchange earnings to finance the imports of intermediate goods.